2008
DOI: 10.1016/j.neulet.2008.01.081
|View full text |Cite
|
Sign up to set email alerts
|

Motor activity induces release of serotonin in the dorsal horn of the rat lumbar spinal cord

Abstract: Literature highlights that serotonergic descending pathways [14] are implicated in somatosensory functions in the spinal cord and that serotonin (5-HT) in the dorsal horn might play a role in motor function through proprioceptive feedback [3,8,9,13]. We hypothesized that 5-HT release in dorsal horn might represent an important factor in the completion of locomotion by facilitation of the spinocerebellar tract [8] and/or by modulation of spinal reflex pathways [9]. The present study demonstrates that during loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 16 publications
2
19
0
1
Order By: Relevance
“…The serotonergic system modulates both nociceptive and motor spinal cord circuits, 28,31,32,39,45,52,57 and motor activity increases the release of serotonin within spinal and supraspinal areas parallel to reduction of mechanical hyperalgesia. 29,33 Moreover, physical exercise decreases NKCC1 levels and restores KCC2 along with recovery of inhibitory reflex responses in spinal cord injured rats. 14 We suggest that the increased activity induced by our treadmill protocol may act similarly by upregulating serotonin activity and may stimulate PKC to restore KCC2-dependent disinhibition to pain after peripheral nerve injury.…”
Section: Possible Role Of Descending Pathwaysmentioning
confidence: 99%
“…The serotonergic system modulates both nociceptive and motor spinal cord circuits, 28,31,32,39,45,52,57 and motor activity increases the release of serotonin within spinal and supraspinal areas parallel to reduction of mechanical hyperalgesia. 29,33 Moreover, physical exercise decreases NKCC1 levels and restores KCC2 along with recovery of inhibitory reflex responses in spinal cord injured rats. 14 We suggest that the increased activity induced by our treadmill protocol may act similarly by upregulating serotonin activity and may stimulate PKC to restore KCC2-dependent disinhibition to pain after peripheral nerve injury.…”
Section: Possible Role Of Descending Pathwaysmentioning
confidence: 99%
“…99 Treadmill stepping for 60 min has also led to increases of serotonin (5-HT) in laminae III-V, possibly from activation of the nucleus raphe magnus during motor training. 100 Serotonergic neurons in certain brainstem nuclei project to the dorsal horn, 101 and decreases in serotoninpositive fibers below the level of SCI are associated with neuropathic pain; intrathecal delivery of 5HT can attenuate allodynia. 102 Engesser-Cessar and colleagues 103 showed that wheel running in SCI mice led to an improvement in locomotion as well as an increase in serotonin-positive fibers below the level of the injury.…”
Section: Figmentioning
confidence: 99%
“…Although there are many studies considering serotonin in nociceptive [22][23][24][25] and motor [26][27][28] modulations, and exercise-induced analgesia [5,6,8,10,29,30], it is important to demonstrate the possible changes to the spinal and supraspinal serotonergic nerve activity in animals submitted to peripheral nervous lesion combined with aerobic exercise training. Thus, this study investigated the effects of aerobic treadmill exercise training on serotonin immunoreactivity patterns in magnus and dorsal raphe nuclei and lumbosacral spinal cord of rats submitted to sciatic nerve transection.…”
Section: Introductionmentioning
confidence: 99%